Social Conflict of the Main Character in Web Series Jingga dan Senja by Kuntz Agus: Sociological Study of Literature on Character Ari) - Fitriyani, Akna; Widyatwati, Ken; Suryadi, M (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study aims to examine the social conflict experienced by the main character named Ari in the web series “Jingga dan Senja” through a sociological approach to literature, based on conflict theory. The purpose of this study is to identify the forms of conflict experienced by Ari's character and analyze the factors underlying the conflict. The research method used is descriptive qualitative. Data analysis is done through identification and classification of data related to types of social conflict. The main data source in this research is the web series “Jingga dan Senja” by Kuntz Agus, while secondary data includes literature studies on literary sociology, social conflict theory, and articles relevant to the web series “Jingga dan Senja”. The data collection technique is done through observation. Note-taking was done to document relevant data, including scene descriptions and transcripts of important dialogues. This research results in the finding that Ari's character faces various types of conflicts. The types of social conflicts that occur in the web series “Jingga dan Senja” include conflicts between individuals, conflicts between groups, conflicts of interest, and conflicts of social institutions. The factors that trigger conflict include internal factors and external factors. Internal factors that trigger conflict include emotional factors, unfaithfulness factors, and perspective factors. Meanwhile, external factors consist of status or position factors and dysfunctional family environment factors that underlie these conflicts.